Data Deduplication for High Performance Storage System - Feng, Dan. (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book comprehensively introduces data deduplication technologies for storage systems. It first presents the overview of data deduplication including its theoretical basis, basic workflow, application scenarios and its key technologies, and then the book focuses on each key technology of the deduplication to provide an insight into the evolution of the technology over the years including chunking algorithms, indexing schemes, fragmentation reduced schemes, rewriting algorithm and security solution. In particular, the state-of-the-art solutions and the newly proposed solutions are both elaborated. At the end of the book, the author discusses the fundamental trade-offs in each of deduplication design choices and propose an open-source deduplication prototype. The book with its fundamental theories and complete survey can guide the beginners, students and practitioners working on data deduplication in storage system. It also provides a compact reference in the perspective of key data deduplication technologies for those researchers in developing high performance storage solutions.
Preface -- Deduplication: Beginning from Data Backup System -- Overview of Data Deduplication -- Chunking Algorithms -- Indexing Schemes -- Rewriting Algorithms -- Secure Deduplication -- Post-deduplication Delta Compression Schemes -- The Framework of Data Deduplication -- References.
Keywords: Information retrieval; Computer architecture; Electronic digital computers-Evaluation.; Computer input-output equipment; Information storage and retrieval systems; Computer systems; Big data; Data Storage Representation; System Performance and Evaluation; Input/Output and Data Communications; Information Storage and Retrieval; Computer System Implementation; Big Data